Strategi Pengembangan Klaster UMKM Menggunakan Metode Analytic Hierarchy Process Di Kabupaten Kutai Timur - Bustomi, Muhamad Yazid; Suryanto, Joko (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2022)
Micro, small and medium enterprises (MSMEs) had an important role in the Indonesian economy, with the creation of domestic products and the ability to absorb labor. In order to maintain the performance of MSMEs to exist and grow up, it was necessary to have a strategy carried out both from internal MSMEs themselves or the stakeholders. The aims of this study was to find out the strategy for developing the MSMEs cluster by using the analytic hierarchy process method. The determination of the sample used was by purposive sampling, namely members of the MSMEs home industry partner of LPB Pabanet, who were active and willing to be respondents with a total of 27 MSMEs. This study used a direct interview to respondents containing questions for clustering MSMEs, then a focus group discussion (FGD) was carried out with experts which aims to explore information used in formulating development strategies of MSME based on clusters. The results showed that based on the analysis using the fuzzy C-means method formed 3 clusters of SMEs. The strategy for the first cluster was on the production process criteria (0,391) with an alternative strategy for obtaining permits of P-IRT (0,351). In second cluster, the criteria with the highest weight was capital (0,395) with alternative strategies for making financial reports regularly (0,863). In the third cluster, the alternative strategy chosen on the marketing criteria (0,547) was to establish a partnership (0,407).